LEGAL STATUS OF ONLINE LOANS (PINJOL) IN THE ISLAMIC PERSPECTIVE OF AHLUSUNNAH WAL JAMA'AH - Sunardi, Sunardi; Muhibbin, Moh.; Amar, Gays (International Significance of Notary, 2022)
The more widespread and demanding times regarding social media are used by some people to market their businesses, including online loans. Now this is the problem that the population of Indonesia is Muslim and many are from the Nahdatul Ulama group, so the writer is interested in writing with the formulation of the problem How is the Legitimacy of Loans (Online Loans) Viewed from Islamic Law and the Views of Aswaja Ulama in Indonesia. And how is the law in the online lending and borrowing system not being paid by the debtor according to the perspective of Islamic law and the scholars'. This study uses a type of normative legal research. The results of this study indicate that: The Legitimacy of Loans (Online Loans) Is Reviewed from Islamic Law and the Views of Aswaja Scholars in Indonesia. The author is of the opinion that borrowing money that is not in accordance with Ahlu Sunnah waljemaah is generally unlawful or unlawful because it is not in accordance with Islamic law, because there are conditions and pillars that are not in accordance with the contract that do not fulfill face to face and there is an element of usury in it even though some of them justify it. various notes. The author also agrees with the fatwa of the Indonesian Ulema Council. He argues that borrowing money is not permissible under Islamic law. However, the law in question is not only illegal online loans; Similar laws also exist for offline or direct loans that contain elements of riba and are therefore not legal according to Islamic law. The law in Islamic Lending and Borrowing Online Systems is not paid by the debtor According to the Perspective of Islamic Law and the Ulama, the author concludes that it is clear in Islamic law that paying legal debt is obligatory even though it is online lending which has been banned through the MUI fatwa and the government has advised not to paying a legitimate loan because it causes a lot of misery to the community with high interest, but in syari' in Islamic law it is mandatory to return or pay off the debt. In Islamic law, debt repayment is not allowed to be added with the intention of benefiting the muqridh, but if the addition is given on the basis of the willingness or sincerity of the muqtaridh with the aim of remuneration, then this is permissible because it is not usury.Keywords: Loans, Online, Islamic Law